Natural deaths in male prisoners: a 20-year mortality study - Fazel, S; Benning, R (Oxford University Press, 2006)
Background: Although morbidity is high in prisoners compared with the general population, uncertainty exists over rates for natural causes of death. We investigated natural deaths in prisons in England and Wales over a 20-year period. Methods: All men who died in English and Welsh prisons from 1978-1997 were identified. All deaths received a post-mortem. Death certificates were obtained to provide mortality information according to ICD-9. Standardised mortality ratios (SMRs) for major causes of natural death were calculated in those <60 years. Results: 574 male prisoners died in custody from natural deaths, of which 307 (53%) deaths were from circulatory diseases and 91 (16%) from respiratory causes. Overall, SMRs for natural deaths were significantly lower than the general population (SMR = 0.70; 95% CI = 0.65-0.76). However, SMRs from respiratory pneumonia (SMR = 2.35; 1.75-3.16) and from other infectious causes were higher (SMR = 1.52; 1.03-2.23). Conclusion: There are important methodological challenges in calculating SMRs in prisoners. Bearing these in mind, we found increased mortality ratios for respiratory pneumonia and other infections. These findings highlight the need for the screening and effective treatment of infectious diseases in prisoners.